Pengaruh Teknik Memuat dan Kompetensi Perwira Dek terhadap Efisiensi Penanganan Muatan Bijih Nikel di Pelabuhan Surigao Filipina - Mujakki; Cahya Fajar Budi Hartanto; Haryani (Politeknik Bumi Akpelni Semarang, 2025)
This study aims to analyze the influence of loading techniques and the competence of deck officers on the efficiency of nickel ore handling at Surigao Port, Philippines. The author employs a quantitative approach with a descriptive research method to present findings based on the collected data. A questionnaire is used as a data collection tool in this research, involving 8 respondents from the crew of MV. Amanah Sulawesi AMC. The obtained data are analyzed using validity tests, reliability tests, normality tests, linear regression analysis, T-tests, and F-tests, with the assistance of SPSS version 25. The analysis results indicate that effective loading techniques and the competence of deck officers have a significant impact on the efficiency of nickel ore loading. From the findings of this study, it can be concluded that the implementation of good loading techniques and the enhancement of deck officer’s competence contribute positively to the efficiency of cargo handling at Surigao Port. This research is expected to provide recommendations for the management of logistics and port operations to improve performance in handling nickel ore cargo.